2022
DOI: 10.1002/prot.26334
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of an N‐acetyltransferase from the human pathogen Acinetobacter baumannii isolate BAL_212

Abstract: Acinetobacter baumannii is a Gram-negative bacterium commonly found in soil and water that can cause human infections of the blood, lungs, and urinary tract. Of particular concern is its prevalence in health-care settings where it can survive on surfaces and shared equipment for extended periods of time. The capsular polysaccharide surrounding the organism is known to be the major contributor to virulence. The structure of the K57 capsular polysaccharide produced by A. baumannii isolate BAL_212 from Vietnam wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Shown in Figure 4 is the initial velocity versus UDP‐GlcNAc3NA concentration for Pcryo_O615. The enzyme demonstrates a catalytic efficiency of 1.1 (±0.2) × 10 4 M −1 s −1 for UDP‐GlcNAc3NA, which is similar to that observed for the N ‐acetyltransferase from the human pathogen A. baumannii isolate BAL‐212 (3.9 × 10 4 M −1 s −1 ) 16 …”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…Shown in Figure 4 is the initial velocity versus UDP‐GlcNAc3NA concentration for Pcryo_O615. The enzyme demonstrates a catalytic efficiency of 1.1 (±0.2) × 10 4 M −1 s −1 for UDP‐GlcNAc3NA, which is similar to that observed for the N ‐acetyltransferase from the human pathogen A. baumannii isolate BAL‐212 (3.9 × 10 4 M −1 s −1 ) 16 …”
Section: Resultssupporting
confidence: 70%
“…The crystals utilized belonged to the P 2 1 space group with six subunits in the asymmetric unit. Previous investigations have shown that the nucleotide‐linked sugar N ‐acetyltransferases function as trimers with C 3 symmetry 16,19–26 . A ribbon representation of one of the trimers is presented in Figure 7a and as can be seen, the active sites are wedged between the subunits.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations